1964
DOI: 10.1029/jz069i019p03927
|View full text |Cite
|
Sign up to set email alerts
|

Solar cycle changes in inner-zone protons

Abstract: Calculations on time dependence of the inner Van Allen belt proton population show that large changes of the population up to a factor of 50 will take place during the solar cycle. The effect is most pronounced for the region of B‐L space corresponding to minimum altitudes of 300–700 km. Because protons of different energies respond to the changing solar cycle at different rates, the proton energy spectrums will change with time also.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

1967
1967
2007
2007

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 20 publications
3
31
0
Order By: Relevance
“…The appropriate results are shown in Figure 9 for the time x Energy,MeV interval of October-November, 1963. In the region of the artificial radiation belt (L~< 1.7) at energy E ~> 2 MeV, the electron spectrum does not contradict, within the experimental errors, the spectrum expected from the decay of the fission fragments soon after the explosion (CARTER et al, 1959). A similar result follows from WEST et al…”
Section: The Energy and Spatial Distribution Of The Radiation In The supporting
confidence: 76%
“…The appropriate results are shown in Figure 9 for the time x Energy,MeV interval of October-November, 1963. In the region of the artificial radiation belt (L~< 1.7) at energy E ~> 2 MeV, the electron spectrum does not contradict, within the experimental errors, the spectrum expected from the decay of the fission fragments soon after the explosion (CARTER et al, 1959). A similar result follows from WEST et al…”
Section: The Energy and Spatial Distribution Of The Radiation In The supporting
confidence: 76%
“…They showed that only part of the changes were adiabatic. At low altitudes the solar cycle effect predicted by Blanchard and Hess (1964) finally has become evident. Nakano and Heckman (1968) have reported the 63 MeV protons with minimum altitudes between 220 and 375 km decreased a factor of 2 between mid 1966 and late 1967 after remaining constant for the previous 3-1/2 yr.…”
Section: Stable: Trapping Regionmentioning
confidence: 99%
“…The proton environment is then proportional, in steady state, to the source (neutron albedo) and the population lifetime (atmospheric interaction) as shown by Blanchard and Hess (1964). The interpolation procedure we will implement assumes a steady state solution to the population kinetic equations as the product of the albedo neutron source and the particle population lifetimes that are proportional to the product of neutron monitor count rate and solar radio output at the 10.7 cm wavelength related to atmospheric heating resulting in expansion.…”
Section: Environmental Model Developmentmentioning
confidence: 99%